TRACK as a complementary tool to GINA and NAEPP guidelines for assessing asthma control in pre-school children. (June 2014) - Kaya, Ayşenur; Erkocoglu, Mustafa; Akan, Aysegul; Vezir, Emine; Azkur, Dilek; Ozcan, Celal; Civelek, Ersoy; Toyran, Muge; Giniş, Tayfur; Misirlioglu, Emine Dibek; Kocabas, Can Naci
Abstract Background: In this study, our goal is to evaluate the consistency between TRACK and the asthma control levels assessed according to the GINA and NAEPP guidelines in children younger than 5 years of age. Methods: Patients under 5 years old, who were followed up for recurrent wheezing for at least 1 year have been included. Parents were given the TRACK questionnaire and the control level of asthma according to GINA and NAEPP guidelines were determined by a pediatric allergist blinded to TRACK scores. Patients were classified into two groups regarding the compatibility of the control level between TRACK and both GINA and NAEPP guidelines. Results: A total of 365 questionnaires were evaluated. The TRACK cut-off point of 80 provided the most consistent balance between sensitivity and specificity for the compatibility with both GINA and NAEPP (for GINA 0.763 and 0.663, kappa = 0.487, p < 0.001 and for NAEPP 0.761 and 0.769, kappa = 0.524, p < 0.001, respectively). When 80 was taken as the cut-off value for TRACK, the compatibility rate of asthma control levels between TRACK and GINA and TRACK and NAEPP was 71.0 and 76.4%, respectively. About 70.1% of the patients who had TRACK scores over 80 and had mild asthma were grouped as controlled according to GINA and 50.0% of patients who had TRACK scores over 80 and had moderate to severe asthma was grouped as uncontrolled according to GINA (p = 0.019). Conclusion: TRACK is compatible with NAEPP and GINA in majority of asthmatic children under 5 years of age. Nevertheless, there is a discrepancy between guidelines and TRACK scores; therefore, it should be used in conjunction with a detailed clinical examination in order to make a better decision for assessing the control levels and management plan.